Rahmah El Yunusiyah: Transformation of Islamic Education and Its Role in Women’s Education in Padang Panjang - Hasibuan, Ahmad Ibrahim (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article discusses one of the reformers in the field of Islamic Education, namely Rahmah El Yanusiyah. Rahmah el-Yunusiyyah was the first person to build a special school for women through the institution she founded. She aspires for women to be able to stand on their own feet (independence) to become mothers, capable educators, active and responsible for the welfare of the nation and homeland, where religious life has a proper place. The research in this paper uses a descriptive qualitative study approach. The data collection stages were carried out systematically and structured. Where data analysis only focuses on Rahma El Yanusiyah's thoughts in the transformation of Islamic Religious Education in accordance with the nation's goals. To present data, researchers used a descriptive approach. The research results provide a solution that the dichotomy problem of science can be answered with scientific transformation, namely integrating classical religious knowledge with general knowledge) and providing skills without rejecting scientific transformation. What is meant by women's education in Padang Panjang, consists of 1) Establishing Madrasah Lil Banat or the First Women's School in Indonesia (Padang Panjang), 2) Becoming a role model and reporter for women's emancipation, and 3) Providing practical skills for women’s.Keywords: Rahmah El Yanusiyah, Islamic Education, Women's Education.Abstrak Tulisan ini membahas salah satu pembaharu di bidang Pendidikan Islam, yaitu Rahmah El Yanusiyah. Rahmah el-Yunusiyyah adalah orang yang pertama mendirikan sekolah yang khusus untuk kaum wanita melalui lembaga yang didirikannya. Ia bercita-cita agar kaum wanita sanggup berdiri di atas kaki sendiri (berdikari) untuk menjadi ibu, pendidik yang cakap, aktif dan betanggung jawab kepada kesejahteraan bangsa dan tanah air, di mana kehidupan agama mendapat tempat yang layak. Penelitian dalam tulisan ini menggunakan pendekatan studi kualitatif yang bersifat deskriptif. Tahapan pendataan dilakukan secara sistematis dan terstruktur. Dimana analisis data hanya berfokus pada pemikiran Rahma El Yanusiyah dalam transformasi Pendidikan Agama Islam sesuai dengan tujuan bangsa. Untuk menyajikan data, peneliti menggunakan pendekatan deskriptif. Hasil penelitian memberikan solusi bahwa masalah dikotomi sains dapat dijawab dengan transformasi ilmiah yaitu mengintegrasikan pengetahuan agama klasik dengan pengetahuan umum) dan memberikan keterampilan tanpa menolak transformasi keilmuan. Sedangkan perannya dalam pendidikan wanita di Padang Panjang, terdiri dari 1) Mendirikan Madrasah Lil Banat atau Sekolah Perempuan Pertama di Indoenesia (Padang Panjang), 2) Menjadi teladan dan pelapor emansipasi perempuan, dan 3) Mengembangkan keterampilan Praktis untuk perempuan.